Bridging Local Wisdom and Modernity: Swamp Buffalo Cultivation in Tampakang Village as a Model of Nature Conservation and Sustainable Community Welfare - Hanafiah, Akhmad; Ashari, Ayu; Nafira, Fathan Azfa; R.B. D, Keukeu Amalia; Al Fitri, Muhammad Rizqi; Fajri, Muhammad Taufik; Husna, Najwa; Azkiya, Nur Anita; Nakayaanni, Putri (Riviera Publishing, 2024)
This journal explores how swamp buffalo cultivation in Tampakang Village, South Kalimantan, is a model for integrating local wisdom and modernity in achieving sustainable development. Through a qualitative descriptive analysis approach, this study reveals the important role of swamp buffalo in maintaining the balance of wetland ecosystems and as a source of livelihood for local communities. By utilizing field observation methods, in-depth interviews, and literature studies, it was found that local wisdom in swamp buffalo cultivation not only preserves local traditions and culture but also provides economic benefits through ecotourism. In addition, challenges in providing feed during the rainy season and limited knowledge of farmers were identified as obstacles that needed to be overcome. However, the opportunity to develop swamp buffalo tourism can improve community welfare through job creation and income increase. This research provides practical recommendations to conserve swamp buffalo cultivation and maximize its potential as a source of sustainable community welfare.